Proceedings of the 2nd Yogyakarta International Seminar on Health, Physical Education, and Sport Science (YISHPESS 2018) and 1s 2018
DOI: 10.2991/yishpess-cois-18.2018.112
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Plyometric Training and Age on The Agility of Silat Fighters

Abstract: This research purpose to compare the effects of plyometric training on the agility of fighters in the age of 12-14 and 14-17 years old. Agility is an essential component in martial arts as it becomes a measure of the quality of martial arts performance. This research is experimental research. The data collection technique was using Hexagonal Obstacle Test. Sixteen subjects in the age of 12-17 years old were randomly assigned. The data analysis technique used two-way ANOVA at significance level 0.05. The analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…In this research, we found that the sprint training protocol used had a positive effect on increasing agility for the players. Our research supports previous research, which concluded that 6-10 weeks of speed training had a positive effect on the performance of young athletes in various sports, such as taekwondo, Pencak silat, and football (Hidayat, 2018;Mathisen, 2016;Mathisen & Pettersen, 2018;Singh & Sathe, 2017). The increased agility of futsal athletes in this research is because the sprint training program involves many movements, such as changes in direction, and other movements, such as acceleration and deceleration; thus, with these movements, the body experiences neuromuscular adaptation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this research, we found that the sprint training protocol used had a positive effect on increasing agility for the players. Our research supports previous research, which concluded that 6-10 weeks of speed training had a positive effect on the performance of young athletes in various sports, such as taekwondo, Pencak silat, and football (Hidayat, 2018;Mathisen, 2016;Mathisen & Pettersen, 2018;Singh & Sathe, 2017). The increased agility of futsal athletes in this research is because the sprint training program involves many movements, such as changes in direction, and other movements, such as acceleration and deceleration; thus, with these movements, the body experiences neuromuscular adaptation.…”
Section: Discussionsupporting
confidence: 89%
“…The increased agility of futsal athletes in this research is because the sprint training program involves many movements, such as changes in direction, and other movements, such as acceleration and deceleration; thus, with these movements, the body experiences neuromuscular adaptation. There is an increase in motor units that produces scientifically proven muscle coordination and increases the agility component (Hidayat, 2018;Mathisen, 2016;Mathisen & Pettersen, 2018;Singh & Sathe, 2017).…”
Section: Discussionmentioning
confidence: 99%